Dust concentrations and respiratory risks in coalminers: key risk estimates from the British Pneumoconiosis Field Research. Issue 6 (18th May 2004) - Soutar, C A; Hurley, J F; Miller, B G; Cowie, H A; Buchanan, D
Abstract : To help inform the setting of dust control standards in coalmines, this brief review summarises the most recent and reliable exposure-response relations, for damaging respiratory effects, derived from the Pneumoconiosis Field Research (PFR). Collecting data over 38 years in the British coal industry, this was a programme of prospective research on the respiratory health of coal miners, characterised by regular health surveys and detailed measurements of dust and silica concentrations in the workplace. Exposure-response relations are presented for coal workers' simple pneumoconiosis category II, progressive massive fibrosis, defined deficits of lung function (FEV1 ), and category II silicosis. This simplified overview provides a guide to the most recent and most reliable estimates from the PFR of dust-related risks of substantial pulmonary disease, and to the magnitude of the effects. Control of dust sufficient to prevent category II simple pneumoconiosis should prevent most cases of progressive massive fibrosis and most dust related large lung function deficits. Where the dust contains high proportions of silica, control to low levels is essential, and even quite brief excursions of silica to high levels must be avoided.